Pemberian Penguatan Verbal dan Non-verbal untuk Meningkatkan Hasil Belajar Siswa dalam Pembelajaran Kepahlawanan dan Patriotisme - Yunanik, Siti (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2019)
[Title: The Provision of Verbal and Non-verbal Reinforcement to Improve Student Learning Achievement in Heroism and Patriotism Subject Matter]. The purpose of this study is to improve student learning achievement on the heroic and patriotism figures subject matter through the provision of verbal and non-verbal reinforcement. This research is a class action research (CAR) with the subject of the research were class IV students in semester 1 of SDN 2 Sandik, amounting to 28 students. Student learning achievement data were collected using test instruments and analyzed descriptively-qualitatively. The results showed that the student learning achievement in the first cycle was in the medium category (mean = 5.50) increased in the second cycle (mean = 8.25) with the good category. The implementation of learning has also increased in each cycle. Based on the results of the study it can be concluded that the provision of verbal and non-verbal reinforcement can improve student learning achievement on the heroic and patriotism figures subject matter at SDN 2 Sandik.